P3 Group B Streptococcal (GBS) disease in UK and Irish infants younger than 90 days, 2014–2015. (27th April 2016) - O'Sullivan, C; Lamagni, T; Efstratiou, A; Patel, D; Cunney, R; Meehan, M; Reynolds, A; Campbell, R; Doherty, L; Boyle, M; Davies, E; Heath, P
Abstract : Aims: To define the burden of group B Streptococcal disease in infants younger than 90 days in 2014–2015; their clinical presentation; the frequency of established risk factors; the mortality and short-term complication rates (at hospital discharge); the responsible serotypes and their distribution. In addition, to compare these parameters to those of the previous national surveillance in 2000–2001. Methods: Prospective, enhanced, active surveillance was undertaken through the British Paediatric Surveillance Unit (BPSU), microbiology reference laboratories and national public health agencies. Cases were identified by paediatricians and microbiologists. Paediatricians reporting a case were asked to complete a questionnaire. Microbiologists were encouraged to report cases through established routine laboratory reporting systems, and to submit all invasive GBS isolates to the relevant Reference Units. Surveillance was then enhanced by reconciling data from the clinicians and laboratory reports with referred isolates. Referral of isolates was further optimised through direct contact with all microbiology departments. Results: In the 13 months from April 2014 817 cases were identified (incidence 0.89/1000 live births, 95% CI; 0.87–0.91). The incidence for early-onset (EO) disease was 0.54/1000 (0.51–0.57), and for late-onset (LO) disease 0.36/1000 (0.33–0.39). Clinical information is currently available for 77% of cases. Serotype information is available for 46% of cases. Of those cases where gestation is available, 21% of EO cases and 40% of LO cases were in infants born prematurely. 36% of EO cases where information is available had one or more risk factors present at or before delivery. There were 147 meningitis cases (55 EO, 92 LO). 38 infants died (4.7%); 16 were EO cases and 22 were LO. Conclusion: Since the national surveillance of 2000–2001 there has been a significant increase in the incidence of invasive GBS disease in all five British Isles countries. There has been a proportionately greater increase in the incidence of LO disease; however the increase was also evident for EO incidence, despite the presence of national prevention guidelines. New strategies for preventing GBS in this age group are urgently required.